Proposals for an organized guidance program and a guidance in-service training course for Saint Louis College of Tuguegarao, Cagayan - Hernandez, Belen V. (Animo Repository, 1974)
This study aims to propose an organized guidance program for the college department of St. Louis College of Tuguegarao. The subjects of this study were the college students of St. Louis College. A questionnaire was devised by the researcher which consisted of 14 student problems or areas of concern that were observed among the students and gathered from discussions with faculty members. These problems were presented to the administration-faculty-staff members and to the students, who were asked to rank the problems according to their perception of its seriousness, and to add other problems they may be concerned about. The teachers were further asked to give their suggestions to meet the problems, and to give their observations regarding the social, cultural, economic and political conditions in the town or province that could have led to the problems of the students. Two separate questionnaires, one for the students and another for the teachers, were administered. To augment data taken from the questionnaires, the Personal Data Blank was also used. The proposed organized program of guidance services, which included the assumptions and principles, general and behavioral objectives, and a consideration of the factors that would limit or favorably affect the proposed program and its future implementation, were presented. The following guidance services were proposed: information, testing, counseling, group Guidance, and the cumulative Record. The roles proposed for the school staff and the proposed organizational chart, facilities, budget, and evaluation procedures were also presented.